THE ROOT CAUSES OF FINANCIAL CRISIS IN ISLAMIC ECONOMIC PERSPECTIVE - Ascarya Ascarya (Universitas Muhammadiyah Prof Dr Hamka, 2017)
The ongoing global financial crisis is just a repeat of financial crises which have occurred one after another since the England crisis in 1825. The crises have subsided in the period under Bretton Woods Agreements (BWA) in 1950-1972, with the implementation of the gold standard. The crises have reemerged with the collapse of BWA in 1971, and up to 2011, there are 421 financial crises covering 147 banking crises, 218 currency crises (10 episodes in 2008-2011), and 66 sovereign debt crisis, including 68 twin crises and 8 triplet crises (Laeven and Valencia, 2012). These repeated man-made financial crises happened due to the transgressions of God’s laws in financial dealings, especially in the abandonment of main pillars of Islamic financial system, namely prohibition of ribā (usury or interest), prohibition of maysir (game of chance or speculation) and prohibition of gharar (excessive uncertainty), in their many forms, as well as due to misbehaviors of economic actors, poor governance and unsustainable fiscal system. This study applies Analytic Network Process (ANP) to determine the main root causes of the financial crisis from Islamic economic perspective which are grouped into five clusters, namely: Misbehavior, External Factor, Poor Governance, Unstable Monetary System and Unsustainable Fiscal System. Each cluster will have six relevant elements obtained from literature and in-depth interviews with several experts. The ANP results show that the main root causes of financial crisis from Islamic economic perspective are Social Instability (External Factor), Speculation (Misbehavior), Ineffective Fiscal System (Unsustainable Fiscal System), Hedonism (Misbehavior), Fractional Reserve Banking System (Unstable Monetary System), Political Instability (External Factor), Corruption (Poor Governance), Interest Rate (Unstable Monetary System), Fiat Money (Unstable Monetary System), and Wrong Man in the Wrong Place (Poor Governance). These main root causes should be removed gradually in order to systematically and gradually improve the stability of financial system so that financial crisis will not reappear again and again in the future.